The epidemiology of postpartum malaria: a systematic review. - Boel, Machteld E. (2014)
Pregnant women are more susceptible to malaria than their non-pregnant counterparts. Less is known about the risk of malaria in the postpartum period. The epidemiology of postpartum malaria was systematically reviewed. Eleven articles fitted the inclusion criteria. Of the 10 studies that compared malaria data from the postpartum period with pregnancy data, nine studies suggested that the risk for malaria infection decreased after delivery. All three studies that compared postpartum data with non-pregnant non-postpartum women concluded that the risk did not return to pre-pregnancy levels immediately after delivery. The results of this review have to be carefully interpreted, as the majority of studies were not designed to study postpartum malaria, and there was large variability in study designs and reported outcomes. Current evidence suggests an effort should be made to detect and radically cure malaria during pregnancy so that women do not enter the postpartum period with residual parasites.